PENGARUH PERTUMBUHAN ASET DAN INTEREST INCOME TERHADAP PROFITABILITAS: - - Melan, Melan; Retnaningdiah, Dian (Kajian Ekonomi dan Bisnis, 2024)
Background: The growth of the economic sector is intricately linked to the crucial function of financial institutions. A bank is a type of financial entity that operates within the banking sector. Banks serve the purpose of collecting funds through savings, deposits, and current accounts, and then distributing those amounts through credit or loans. Banks exert a significant impact on economic development. Objective: The objective of this study is to examine the impact of asset growth and interest income on profitability. Method: This study was a quantitative study that used an associative technique to assess variables partially and concurrently within the population of Bank BTN listed on the IDX from 2019 to 2023. The sampling process employed non- probability sampling approaches, specifically the purposive sampling method. Result: The findings indicate that asset growth (X1) does not have significant effects on profitability (Y), however interest income (X2) has a significant impact on profitability (Y). Additionally, there is no simultaneous effect of asset growth (X1) and interest income (X2) on profitability (Y). Conclusion: The results of this study can be concluded 1. Asset growth (X1) does not have a partial effect on profitability (Y) 2. Interest income (X2) has a significant partial effect on profitability (Y) 3. Asset growth (X1) and interest income (X2) do not have a simultaneous effect on profitability (Y).   Keywords: Asset Growth, Interest Income, Profitability